BUSINESS PLANNING PROBLEMS OF ENTERPRISE DEVELOPMENT - VITIUK, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The historical prerequisites for the development of business planning in Ukraine are revealed. A number of differences in writing business plans in Ukraine and abroad are established. The decisive influence of war on the formation of business plans for enterprise development is proven. It is established that in modern economic conditions, the main attention when implementing business planning should be paid to the influence of hostilities and their consequences, the increase in migration processes, logistics, changes in the structure of demand for goods and the solvency of customers. It is revealed that as a result of military-political changes, changes have occurred in the buyers of enterprises, in particular, a new “consumer” has emerged - war, which additionally actualized the need for the development of all related industries and services; the state has become the main customer of many high-value, intellectual goods for the needs of the front; a new consumer has emerged - a volunteer and a new source of financing - donations. It is proved that the main non-deterministic factors influencing the implementation of business planning are scientific and technological progress, geopolitical situation, speed of enterprise reaction to events and processes, change of importance of scale to flexibility. A set of problems of Ukrainian enterprises that hinder effective business planning has been identified, which, along with traditional economic conditions, are supplemented by new military circumstances. The need to make changes to the traditional content of writing a business plan has been proven. The following management measures have been proposed to establish the correct presentation of information in a business plan in order to ensure its effectiveness in war conditions: use of accurate and timely information, creation of trust between business partners, effective risk management, ensuring efficiency and productivity, maintaining a stable reputation of the enterprise, ensuring the effectiveness of internal communication and increasing competitiveness.